Kualitas hidup lansia hipertensi dengan overweight dan tidak overweight - Tri Mei Khasana; Nyoman Kertia; Probosuseno Probosuseno (Jurnal Gizi Klinik Indonesia, 2020)
The quality of life in elderly hypertension with overweight and non-overweightBackground: Indonesia will enter the period of aging and an increase in several elderlies with chronic diseases. The biggest health problems of the elderly are degenerative diseases, namely hypertension which significantly disrupts the quality of life both in terms of physical and mental health. One of the causal conditions associated with hypertension is overweight and obesity, which is known at this time the prevalence of obesity is growing progressively in old age. However, the results of research related to the influence of obesity on quality of life are still controversial.Objective: To determine differences in quality of life between hypertensive elderly who are overweight and non-overweight.Method: Cross-sectional study conducted in Yogyakarta City in Januari-April 2017 with a subject of 200 elderly people aged 60-74 years. Overweight was determined based on BMI measurements (>23 kg/m2) with an estimation of elderly height using depa length, quality of life of the elderly was measured using WHOQOL-BREF questionnaire, and compared the quality of life by age, gender, education, occupation, income, marital status, comorbidity, and disease history. Data analysis used independent t-test and linear regression.Results: Mean of environmental domain score was significantly higher (p=0,012) in elderly hypertension with overweight (26,69±3,28) compared to elderly hypertension non-overweight (25,44±3,58). Overweight protective effect on the low quality of life of the environment domain because it is influenced by other factors such as marital status, income, and education. Multivariate analysis shows that income and marital status are external factors that consistently influence the quality of life of the elderly both in total scores and per domain. High-income elderly people with married status have a better quality of life score.Conclusions: The mean score of the environmental domain is higher in elderly hypertension with overweight. Quality of life scores will be better in high income elderly and married.